PENGARUH GAME EDUKASI QUIZIZZ TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS IV - Septiani, Dias; Herli Sundi, Venni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem behind this research is the unavailability of learning media that is used as a support for the main media that can make it easier for students to understand the subject matter taught by the teacher, especially learning media that is creative, varied, and interesting for students. The purpose of this study was to determine the difference between the experimental class and the control class using the quizizz educational game on the critical thinking ability of fourth grade mathematics students and how much the quizizz educational game affects students' critical thinking. This research was conducted at SD Negeri Kalibata 07 in early November to December 2023, with the research target of class IV totaling 54 students, 27 experimental classes, and 27 control classes using quota samples. The method used in this research is quantitative experiment quasi experiment type and with posttest only control group design. The data collection techniques used were observation, tests, and documentation. Then the data was analyzed and processed using SPSS version 22. The results of hypothesis analysis using the T test prove that there are differences between experimental classes and control classes using quizizz educational games on students' critical thinking skills.